Design of Aceh Government's Dayah - Muhammad Anggung Manumanoso Prasetyo; Zulkhairi Zulkhairi (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2022)
The difference in boarding school management characteristics in Aceh significantly contrasts with other provinces is the Board of Education/Dayah Office. Through the Dayah Region, the Aceh government has border boarding schools in four districts (Aceh Tamiang, Aceh Singkil, Southeast Aceh and Subulussalam City). The borders aim to fortify the encroachment of Muslims in the border region through educational access. This research is comparative qualitative research. Data sources were obtained from descriptive written and oral data and observed people and their behaviour. The presentation of research data is presented through data classification, general characteristic conclusions, propositions, and theories. Inductive techniques of analysis do the writing. This writing is expected to be a reference for the government in fostering boarding schools and managers generally in improving the effectiveness of boarding schools. The results of the study show a Border Power management model reviewed from managerial functions, namely planning operations in primary strategic plans; leadership functions lead to cooperation and participative styles; implementation functions (management sites) integrate between salafy-modern- and government and evaluative processes in organizational development concepts that prioritize on aspects of HR, economics and infrastructure mean. Implementing management on each border as a government boarding school is already underway, effectively referring to empirical data, the quality and quantity of Dayah Perbatasan are superior to the other educational institutions in their respective districts.